Calculation of the stress-strain state, creep and creep-damage of multilayer plates on the elastic foundation - Богомолов, В. А.; Склепус, С. Н. (Інститут енергетичних машин і систем ім. А. М. Підгорного Національної академії наук України, 2014)
The paper considers the problem of calculating the stress-strain state, creep and creep-damage of multilayer orthotropic plates on elastic foundation. Plate may be loaded by the transverse load, normal and tangential contour loads and the temperature field. A variational formulation of the problem is made in the terms of refined theory of plates and shells. Cauchy problem in time for the main unknown functions of initial-boundary value problem is formulated. To solve the nonlinear initial-boundary creep and creep-damage problem is proposed to use a combination of R-functions, Ritz and Runge-Kutta-Merson methods. R-functions method allows to accurately account for the geometry of the domain and the boundary conditions of the most general form. The solution of the boundary value problem is represented as a formula - structure of the solution that exactly satisfies all (general structure of the solution) or part (partial structure of the solution) boundary conditions. Structure of solution is invariant with respect to the shape of the domain. An example of calculating of stress-strain state of two-layer plate on elastic foundation has been shown. The developed method can be used to investigate the stress-strain state and the long-term strength of road surface.